A Classification Review of Hadith Research in Indonesia - Wahyudin Darmalaksana (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The abundance of hadith research demands a classification to sustain the discipline of hadith studies. This study aims to conduct a classification review on hadith research. The method used is qualitative through a literature review and employs a content analysis. The result shows some findings and discussions regarding the distribution, classification, and implication of hadith research. This study concludes that the classification of hadith research is significant for its enthusiasts to discern a position in sustainable research. Hence, this necessitates a formulation for hadith research development in the Department of Hadith Studies in Islamic higher education institutions in Indonesia.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//